2021
DOI: 10.3389/fimmu.2021.750407
|View full text |Cite
|
Sign up to set email alerts
|

New Artificial Intelligence Score and Immune Infiltrates as Prognostic Factors in Colorectal Cancer With Brain Metastases

Abstract: Incidence of brain metastases has increased in patients with colorectal cancer (CRC) as their survival has improved. CD3 T-cells and, lately, DGMate (DiGital tuMor pArameTErs) score, have been identified as prognostic factors in locally advanced CRC. Until now, there is no data concerning the prognostic value of these markers in patients with CRC-derived brain metastases. All consecutive patients with CRC-derived brain metastases diagnosed between 2000 and 2017 were retrospectively included. Staining for CD3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Complete response (CR): All target lesions disappeared completely ( 2 ). Partial response (PR): The total diameter of the target lesion was reduced by ≥30% ( 3 ). Progressive disease (PD): The total diameter of the target lesion increased by ≥20% ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete response (CR): All target lesions disappeared completely ( 2 ). Partial response (PR): The total diameter of the target lesion was reduced by ≥30% ( 3 ). Progressive disease (PD): The total diameter of the target lesion increased by ≥20% ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of CR+PR is defined as the objective response rate (ORR), while the ratio of CR+PR+SD is defined as the local control rate (LCR). Radiation-induced brain necrosis was diagnosed when at least 2 of the criteria listed below were fulfilled ( 8 ) ( 1 ): On enhanced MRI or CT images, the lesions showed irregular borderP enhancement with obvious oedema ( 2 ); MRI or CT perfusion imaging showed hypoperfusion in the lesion ( 3 ); MRS suggested a decreased Cho value in the enhanced area ( 4 ); PET revealed that the uptake of 18 F-FDG in the enhanced area was significantly decreased. Overall survival (OS) was defined as the time from the diagnosis of brain metastasis to death or the end of the follow-up period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are the most studied TIME-associated immune cells and play important parts in the anti-tumor immune response [97]. Studies have found that CRC tumors with fewer tumorinfiltrating T cells are not sensitive to radiotherapy [98][99][100][101]. With regard to T cell subtypes, lower proportions of CD4+ T and CD8+ T cells have been observed in the TIME of radiotherapy-resistant CRC tumors [54,91,[102][103][104][105][106][107][108], with a greater proportion of regulatory T cells (Tregs) [75,[109][110][111].…”
Section: B Lymphocytes and T Lymphocytesmentioning
confidence: 99%
“…PRKCSH expression is correlated with immune cell infiltration in patients with lung carcinoma Previous studies have reported that the survival time of cancer patients depends on the quantity and activity of tumour-infiltrating lymphocytes. 24,25 Therefore, we used the TIMER database to investigate the association between PRKCSH expression and immune cell infiltration in various types of cancer. We found that PRKCSH expression levels in bladder urothelial carcinoma, breast invasive carcinoma, LUAD, and lung squamous cell carcinoma cancer tissues were negatively correlated with tumour purity and the infiltration of B cells, CD8 + T cells, CD4 + T cells, macrophages, neutrophils, and dendritic cells (Fig.…”
Section: Alterations In Prkcsh Expression Have Prognostic Value In Lu...mentioning
confidence: 99%